Optimal International Financial Cooperation: Solution To The Growing Breakdown Of Global Cooperation - Nasution, Chairuddin Syah (Universitas Muhammadiyah Yogyakarta, 2018)
International Financial Cooperation today may require a more complex preparation than ever, particularly in the era of globalization. It is known that the global economy may bring about changing socio-economic, cultural, technological, and political condition of many countries, whilst the globalization itself has often surpassed domestic circumstances among nations which consequently leads to the need of providing a more advance principles of international financial cooperation. Regardless to these changing circumstances, the international financial cooperation may differ in nature which relatively depends on the types and objectives of the international institution involved. On the other sides, the literatures on international policy coordination are vast and multifaceted (there is no one size fits for all). However, there are some basic conditions that can be shared in common. Based on the study of various literatures, it is found that the challenges of international financial cooperation today may encircle not only about the readiness of the nation states, institutions, and related projects in utilizing the international financial cooperation, but it may also include other variuos aspects such as an optimal structure of cooperation agreement, a pattern of compliance with cooperation agreements, principles for cross border cooperation on crisis management, sharing rules of the costs of future interventions, and perhaps specific issues and barriers. All of these challenges and barriers certainly need coordinated actions to ensure that the optimal objectives of the international financial cooperation are achieved. Thus, these pre-requisite conditions should be embraced in the more advance guiding principles of the international financial cooperation. As such, the relevant authorities, including supervisory agencies, central banks, and finance ministries will also be able to tackle a severe stress in case of sudden financial crisis and managing them successfully.